Teacher Professional Development Models and Practices in Foreign Educational Systems - L. Yu. Gracheva; E. R. Bagramyan; М. N. Tsygankova; Т. Ts. Dugarova; N. N. Sheveleva (Russian State Vocational Pedagogical University, 2020)
Introduction. The formation and implementation of the national teacher growth system (NTGS) in the Russian Federation involves global practices, which are based on effective teacher professional development models. The present research analyses approaches and models used in the training and continuing professional development of teachers in Hong Kong and Finland.The aim of the current article is to identify the meaningful issues of the formation of a teacher growth national system in the context of the best foreign experiences, as well as to reveal the possibilities, which allow applying these effective experiences to Russian realities.Methodology and research methods. In the course of the study, the authors relied on a socio-cultural approach to the organisation of the additional professional pedagogical education, the concept of continuing and non-formal learning throughout life, as well as methodological approaches and methods developed and applied in comparative pedagogy. Understanding and summarising the content of the research materials was carried out on the basis of a comparative retrospective analysis with a search depth of 10-12 years.Results. The analysis of effective models of teacher professional growth and development in Hong Kong and Finland has revealed the following similar positions: strict selection rules and requirements for teaching major and specialties; expanding the component of teaching practice in the learning process; inclusion of the research-based component in training programmes at university and post-graduate levels of teacher professional development; actualisation of the problems concerning specific groups of teachers; creation of continuing (life-long) teacher professional development systems; awareness of the special relevance of "entry into the profession" programmes as a dynamically developing component in the teacher continuing professional growth; creation of specific motivation mechanisms for successful professional teaching activities, which are based on national historical and cultural characteristics and values.Scientific novelty. The main stages, modules, key characteristics of teacher professional development models in Hong Kong and Finland are analysed systematically. The peculiarities of teacher professional development practices, which are widespread in Anglosphere, are revealed in terms of Hong Kong realities. The motivation mechanisms for effective teacher professional activities, which are based on national cultural and historical values, have been described. The similarities and differences in the application of these mechanisms are demonstrated.Practical significance. The results and conclusions of the research undertaken by the authors can be put into the basis for further reforms aimed at the formation and implementation of the teacher growth national system in the Russian Federation. Also, these research findings have important implications to create the mechanisms for adapting teachers to changes and to increase their motivation for continuing professional growth.